2008
DOI: 10.4002/0076-2997-50.1-2.331
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Caused Confusion: On the Systematics Of the Freshwater Gastropod Sulcospira pisum (Brot, 1868) (Cerithioidea, Pachychilidae)

Abstract: We document a case of shell convergence in sympatric freshwater cerithioidean gastropods that has caused confusion in traditional classifications emphasizing shell features. Based on the comparative study of the operculum, radula, and embryonic shell obtained from dry remains of soft bodies, we present evidence that "Melania" pisum is not а thiarid species closely related to Balanocochlis glans (Busch, 1842), as has been supposed with respect to the very similar shells of both species. The species is transferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…However, even the most pronounced of these conchological features, such as e.g. shell size, shape and sculpture as well as colour, hardly allow for definite species identifications, as was exemplified among the freshwater Cerithioidea for Melanopsidae (Glaubrecht 1993(Glaubrecht , 1996 and Pachychilidae Kaehler & Glaubrecht 2001, 2006Kaehler et al 2008). In this context, we found in the present study on Australian Thiaridae that the use of conchological features is of limited use only.…”
mentioning
confidence: 54%
“…However, even the most pronounced of these conchological features, such as e.g. shell size, shape and sculpture as well as colour, hardly allow for definite species identifications, as was exemplified among the freshwater Cerithioidea for Melanopsidae (Glaubrecht 1993(Glaubrecht , 1996 and Pachychilidae Kaehler & Glaubrecht 2001, 2006Kaehler et al 2008). In this context, we found in the present study on Australian Thiaridae that the use of conchological features is of limited use only.…”
mentioning
confidence: 54%
“…Köhler et al . ). The present example demonstrates how deceiving similar shells can be in a non‐cladistic framework even in the presence of conflicting evidence from other anatomical characters, such as penial morphology.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to the species level, shell characters are of little value for the delimitation of genera within the Pachychilidae (Köhler & Glaubrecht, 2006, 2007; Köhler et al. , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies concluded that mitochondrial markers may have limited utility in assessing status at the species level for a number of reasons. In contrast to the species level, shell characters are of little value for the delimitation of genera within the Pachychilidae (Köhler & Glaubrecht, 2006Köhler et al, 2008). Similarly, neither the operculum, the radula, nor the midgut morphol-ogy provide good means for this purpose as they are widely conserved within the Pachychilidae and show predominantly symplesiomorphic character states.…”
Section: Systematic Significancementioning
confidence: 99%
See 1 more Smart Citation